STUDI KUALITATIF : PERSEPSI IBU TERHADAP PENGGUNAAN RENDAMAN AIR RUMPUT FATIMAH UNTUK MEMPERCEPAT KONTRAKSI PERSALINAN - Setianingsih, Nida Nabilah; Halizah, Amilatun Nur; Risky, Aulia Dwi Nur; Kharisma, Fian Ninda; Amani, Revani Sabika; Ayara, Shofiyah; Iskandar, Syifaa Alviyana (Universitas Negeri Malang, 2024)
Fatimah grass or Anastatica hierochuntica is a traditional medicinal plant which is believed to speed up the birthing process and reduce the risk of bleeding if the water soaked in it is consumed by pregnant women. The natural phytochemical compounds and flavonoids contained in it can increase the responsiveness of the uterus to oxytocin, thus triggering the labor process. However, research also shows that fatimah grass has side effects such as poisoning the fetus and even miscarriage. The aim of this research is to explore the perspective of pregnant women regarding the use of Fatimah grass to speed up contractions during labor. The method used is a descriptive qualitative research method with interview techniques. The criteria for respondents in this study were mothers who had experienced a vaginal birth (normal), whether they consumed fatimah grass or not, who lived in rural and urban areas. The results of the study showed that respondents who consumed fatimah grass soaked water and those who did not consumed it had varying perspectives. However, all respondents agreed that listening to the doctor's advice was a wiser choice so that the birthing process went more smoothly. This research shows that fatimah grass consumption can be influenced by various factors, such as traditional beliefs, personal experience, information obtained from various sources, and safety considerations.